2014
DOI: 10.1103/physrevb.90.155124
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Bi bilayers on the topological states ofBi2Se3: A first-principles study

Abstract: Bi 2 Se 3 is a three-dimensional topological insulator which has been extensively studied because it has a single Dirac cone on the surface, inside a relatively large bulk band gap. However, the effect of two-dimensional topological insulator Bi bilayers on the properties of Bi 2 Se 3 and vice versa, has not been explored much. Bi bilayers are often present between the quintuple layers of Bi 2 Se 3 , since (Bi 2 ) n (Bi 2 Se 3 ) m form stable ground-state structures. Moreover, Bi 2 Se 3 is a good substrate for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 39 publications
4
18
0
Order By: Relevance
“…It should be noted that our calculated dispersion curves are in disagreement with those published by Eich et al [39], who found a bismuth BL to be located 4.4Å above the substrate. However, our results are in good agreement with those of two other recent theoretical studies concerning the band dispersion, Dirac cone spin texture and its real-space localization [40,41]. In addition, we find excellent agreement of our dispersion curves with experimental ones collected in a photoemission study by Miao et al [41].…”
Section: Theorysupporting
confidence: 82%
“…It should be noted that our calculated dispersion curves are in disagreement with those published by Eich et al [39], who found a bismuth BL to be located 4.4Å above the substrate. However, our results are in good agreement with those of two other recent theoretical studies concerning the band dispersion, Dirac cone spin texture and its real-space localization [40,41]. In addition, we find excellent agreement of our dispersion curves with experimental ones collected in a photoemission study by Miao et al [41].…”
Section: Theorysupporting
confidence: 82%
“…In this case the bands are shifted upward as shown in figures 4(c) and (d). In previous numerical studies the effective electric field responsible for the BB was controlled by a charge transfer originating from a sheet of adatoms located above the Bi2Se3 surface [23][24][25]32]. In these calculations additional SSs were identified in the band structure being attributed to the presence of the given adatoms.…”
Section: Charge Dopants On the Surface Of The Bi2se3 Crystalmentioning
confidence: 94%
“…Besides these comprehensive experimental studies, numerous theoretical works were also devoted to the description of the physical properties of the 2GTIs, including first principle calculations [1,[20][21][22][23][24][25], tight binding [23,26,27] or effective continuous [11] models. The structure of the 2GTIs can be described by a sequence of weakly bound quintuple layers (QLs), each consisting of five atomic layers.…”
Section: Introductionmentioning
confidence: 99%
“…A periodic buckling of the lattice is found beginning from deposition of the 2 nd BL and lasting until the 5 th BL is deposited. The Bi BL lattice gradually relaxes to become bulk-like at a coverage of 24 BLs.…”
Section: Introductionmentioning
confidence: 99%
“…An interesting aspect of the Bi/Bi2Se3 system is the unique stability of a single deposited BL. Density functional theory (DFT) calculations show that the single BL-terminated structure has a lower surface energy than the bare Se-terminated surface [21,22] and there is a stronger bonding between a QL and a Bi BL than there is between QLs [23,24]. In support of this notion, Bi2Se3 surfaces terminated with a single Bi BL have been found to spontaneously form on in-situ [22] and ex-situ [25] cleaved samples.…”
Section: Introductionmentioning
confidence: 99%